2012
DOI: 10.1159/000333035
|View full text |Cite
|
Sign up to set email alerts
|

The Novel WHO 2010 Classification for Gastrointestinal Neuroendocrine Tumours Correlates Well with the Metastatic Potential of Rectal Neuroendocrine Tumours

Abstract: Background: Approximately 10–15% of gastroenteropancreatic neuroendocrine tumours (NETs, carcinoids) occur in the rectum, some of which are potentially able to metastasize. The new WHO 2010 classification of NETs applies to all gastroenteropancreatic NETs, but no reports have studied its correlation with the prognosis of rectal NETs. Patients and Methods: We retrospectively classified 73 rectal NETs according to the novel WHO 2010 and the previous WHO 2000 classifications. The aim was to assess the validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 52 publications
0
56
0
2
Order By: Relevance
“…G3, on the other hand, is a small-cell and large-cell neoplasm subtype (6)(7)(8). In a study of Jernman et al (15) classification was found to be more beneficial in predicting the potential of metastasis of the neuroendocrine tumors compared to the WHO 2000 classification. In a study of Endo et al (16) in 22 gastric neuroendocrine tumors, 81 cases were G1, 5 were G2, and 16 were NEC.…”
Section: Discussionmentioning
confidence: 96%
“…G3, on the other hand, is a small-cell and large-cell neoplasm subtype (6)(7)(8). In a study of Jernman et al (15) classification was found to be more beneficial in predicting the potential of metastasis of the neuroendocrine tumors compared to the WHO 2000 classification. In a study of Endo et al (16) in 22 gastric neuroendocrine tumors, 81 cases were G1, 5 were G2, and 16 were NEC.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 64 paired tumor tissues and adjacent non-tumorous tissues were obtained from paraffin-embedded tissues of patients with GEP-NET (gastric, colorectal or pancreatic NET) who had undergone surgical resection at the Affiliated Hospital of Nantong University (Nantong, China) between January 2009 and January 2014 and had been evaluated and classified according to the WHO 2010 classification (18). The tumor grading of these cases was based on proliferation and mitotic count.…”
Section: Methodsmentioning
confidence: 99%
“…During the last three decades, however, the reported incidence of GEP-NETs has increased worldwide due to improvements in diagnostic tools and clinical awareness of them (15). According to the latest 2010 World Health Organization (WHO) classification (18), GEP-NETs are divided into three types, namely well-differentiated NET, poorly differentiated neuroendocrine carcinoma and mixed adenoneuroendocrine carcinoma, and their pathology can be further graded as G1 [<2 mitoses/10 high power fields (HPFs) and/or Ki-67 index ≤2%], G2 (2-20 mitoses/10 HPFs and/or Ki-67 index between 3 and 20%) and G3 (≥21 mitoses/10 HPFs and Ki-67 index >20%) (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO classification released in 2010, they are categorized into three groups according to their pathological features (2). The incidence of NETs in each organ is unclear.…”
mentioning
confidence: 99%
“…The survival of a patient with NET differs among each pathological grade. Patients with colorectal NET G1 have the most beneficial 5-year survival from 92.1% to 100% (2,4), followed by those with NET G2. Even patients with neuroendocrine carcinoma (NET G3), the most aggressive subtype of NET, have a postoperative 5-year survival of 26.3-57.4% when distant metastasis is absent (5).…”
mentioning
confidence: 99%